Redescription of Lamanema chavezi by optical microscopy and scanning electron microscopy - Angulo T., José (2015)
This study aimed to morpho-anatomically redescribe Lamanema chavezi in the three parasitic stages (egg, third stage larvae and adult) using optical microscopy and scanning electron microscopy. Samples were collected from alpacas (Vicugna pacos) in the municipal slaughterhouse of Melgar province, Puno, Peru. Adult specimens were collected from the small intestine using the Travassos method; eggs were collected from stool samples in infected animals by the flotation technique; and some of the collected eggs were incubated for obtaining larvae by mechanical process. The main findings include the presence of foliated crown rudiment, six cephalic papillae, synlophe ridges features, presence of papillae on the bursal dorsal side in the lateral lobes, spicules alae characteristics, and eggs and L3 larvae features. The results allowed the phenotypic characterization and complement the knowledge of the morpho-anatomy ofL. chavezi for diagnostic purposes and sets a taxonomic level.